2018
DOI: 10.1002/ajb2.1111
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and diversification history of the large Neotropical genus Philodendron (Araceae): Accelerated speciation in a lineage dominated by epiphytes

Abstract: Philodendron is a species-rich Neotropical lineage that diverged from Adelonema during the late Oligocene. Within Philodendron, the three subgenera currently accepted are recovered in two lineages: one contains the subgenera Meconostigma and Pteromischum and the other contains subgenus Philodendron. The lineage containing subgenera Meconostigma and Pteromischum underwent a consistent diversification rate. By contrast, a diversification rate upshift occurred within subgenus Philodendron ~12 mya. This diversific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Moreover, annonex2embl has been employed by several molecular phylogenetic investigations to facilitate their sequence submissions to ENA. Specifically, the software has so far been used in Roy et al (2017), Korotkova et al (2018), Canal et al (2018), Borsch et al (2018), andFalcon-Hidalgo et al (2019) to submit DNA sequence data via the Webin submission portal.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, annonex2embl has been employed by several molecular phylogenetic investigations to facilitate their sequence submissions to ENA. Specifically, the software has so far been used in Roy et al (2017), Korotkova et al (2018), Canal et al (2018), Borsch et al (2018), andFalcon-Hidalgo et al (2019) to submit DNA sequence data via the Webin submission portal.…”
Section: Resultsmentioning
confidence: 99%
“…These subgenera are phylogenetically supported (e.g. monophyletic) but details of their interrelationships are yet unresolved (Canal et al 2018;Sakuragui et al 2018). Consequently, the subgenus Meconostigma has been recognized as the new genus Thaumatophyllum Schott by some authors (Sakuragui et al 2018) but not by others (Canal et al 2018;Boyce and Croat 2020).…”
Section: Introductionmentioning
confidence: 99%
“…monophyletic) but details of their interrelationships are yet unresolved (Canal et al 2018;Sakuragui et al 2018). Consequently, the subgenus Meconostigma has been recognized as the new genus Thaumatophyllum Schott by some authors (Sakuragui et al 2018) but not by others (Canal et al 2018;Boyce and Croat 2020). Whatever the taxonomic status, all the studies on the reproductive ecology of Philodendron have demonstrated that pollination occurs at dusk or early evening and is exclusively attributed to cyclocephaline scarab beetles (Melolonthidae, Dynastinae, Cyclocephalini) (Moore et al 2013;Gibernau et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, EMBL2checklists was employed for the preparation of hundreds of DNA 291 sequences used in two plant phylogenetic and one fungal metagenomic 292 investigation [46][47][48]. The two plant phylogenetic investigations utilized common plant 293 DNA barcoding markers to infer the phylogenetic history of select plant lineages [46,47]. 294 The fungal metagenomic investigation utilized nrDNA barcodes to characterize 295 arbuscular mycorrhizal soil fungi [48].…”
mentioning
confidence: 99%
“…Upon 382 processing with EMBL2checklists, the user receives a checklist that can be directly 383 uploaded to ENA or further edited with a common spreadsheet editor. The utility of 384 EMBL2checklists is best illustrated by its application during the submission preparation 385 of hundreds of DNA sequences submitted to ENA during the publication process of 386 several recent investigations [46][47][48]. With the development of EMBL2checklists, we 387 hope to provide a useful software tool to plant biologists and bioinformaticians alike, 388 increase the amount of sequence data deposited to public sequence databases [7] and 389 advance the idea of publicly-shared research data [9,10].…”
mentioning
confidence: 99%